Hereditary diffuse gastric cancer: updated clinical practice guidelines. Issue 8 (August 2020) - Blair, Vanessa R; McLeod, Maybelle; Carneiro, Fátima; Coit, Daniel G; D'Addario, Johanna L; van Dieren, Jolanda M; Harris, Kirsty L; Hoogerbrugge, Nicoline; Oliveira, Carla; van der Post, Rachel S; Arnold, Julie; Benusiglio, Patrick R; et al.
Abstract: Hereditary diffuse gastric cancer (HDGC) is an autosomal dominant cancer syndrome that is characterised by a high prevalence of diffuse gastric cancer and lobular breast cancer. It is largely caused by inactivating germline mutations in the tumour suppressor gene CDH1, although pathogenic variants in CTNNA1 occur in a minority of families with HDGC. In this Policy Review, we present updated clinical practice guidelines for HDGC from the International Gastric Cancer Linkage Consortium (IGCLC), which recognise the emerging evidence of variability in gastric cancer risk between families with HDGC, the growing capability of endoscopic and histological surveillance in HDGC, and increased experience of managing long-term sequelae of total gastrectomy in young patients. To redress the balance between the accessibility, cost, and acceptance of genetic testing and the increased identification of pathogenic variant carriers, the HDGC genetic testing criteria have been relaxed, mainly through less restrictive age limits. Prophylactic total gastrectomy remains the recommended option for gastric cancer risk management in pathogenic CDH1 variant carriers. However, there is increasing confidence from the IGCLC that endoscopic surveillance in expert centres can be safely offered to patients who wish to postpone surgery, or to those whose risk of developing gastric cancer is not well defined.